The moral impossibility of the existence of drama: notes on the Ollantay controversy (Anclajes, 2020)
In the mid-nineteenth century, a broad exchange of thought on indigenous literature in the Americanist context was unleashed following publication of the Incan drama Ollantay. In 1881, Bartolomé Mitre rose as a dissonant voice in the debate by questioning its particular representations of language, literature, and indigenous cultures, while also challenging the status of pre-Hispanic works. In reviewing these discussions, we approach the problem of Ollantay through his theoretical proposals and the publication of “Ollantay: Estudio sobre el drama quechua”, inserted into his posthumous work Catálogo razonado de la sección lenguas americanas (1909-1911). Analyzing these works, we also seek to convey philological science’s reception in the River Plate literate circle. In particular, we delve into the problems that emerged at that time as issues in anthropological science and which were supported, with varying foci, by indigenous American linguistics.
Keywords: Ollantay; Bartolomé Mitre; indigenous languages and literature; 19th century